No Influence of Transcutaneous Electrical Nerve Stimulation on Exercise-Induced Pain and 5-Km Cycling Time-Trial Performance - Hibbert, Andrew W.; Billaut, François; Varley, Matthew C.; Polman, Remco C. J. (Frontiers in Physiology, 2017)
Introduction: Afferent information from exercising muscle contributes to the sensation of exercise-induced muscle pain. Transcutaneous electrical nerve stimulation (TENS) delivers low–voltage electrical currents to the skin, inhibiting nociceptive afferent information. The use of TENS in reducing perceptions of exercise-induced pain has not yet been fully explored. This study aimed to investigate the effect of TENS on exercise-induced muscle pain, pacing strategy and performance during a 5-km cycling time trial (TT). Methods: On three separate occasions, in a single-blind, randomized and cross over design, 13 recreationally active participants underwent a 30-min TENS protocol, before performing a 5-km cycling TT. TENS was applied to the quadriceps prior to exercise under the following conditions; control (CONT), placebo with sham TENS application (PLAC), and an experimental condition with TENS application (TENS). Quadriceps fatigue was assessed with magnetic femoral nerve stimulation assessing changes in potentiated quadriceps twitch force at baseline, pre and post exercise. Subjective scores of exertion, affect and pain were taken every 1-km. Results: During TTs, application of TENS did not influence pain perceptions (P = 0.68, ηp2 = 0.03). There was no significant change in mean power (P = 0.16, ηp2 = 0.16) or TT duration (P = 0.17, ηp2 = 0.14), although effect sizes were large for these two variables. Changes in power output were not significant but showed moderate effect sizes at 500-m (ηp2 = 0.10) and 750-m (ηp2 = 0.10). Muscle recruitment as inferred by electromyography data was not significant, but showed large effect sizes at 250-m (ηp2 = 0.16), 500-m (ηp2 = 0.15) and 750-m (ηp2 = 0.14). This indicates a possible effect for TENS influencing performance up to 1-km. Discussion: These findings do not support the use of TENS to improve 5-km TT performance.